2017
DOI: 10.1111/jfbc.12371
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR-based metabolic investigation of the effect ofLentinula edodes-derived polysaccharides on aged mice

Abstract: Few comprehensive metabolic profiles of Lentinula edodes‐derived polysaccharides on mammalians have been reported to date. In previous studies, a novel heteropolysaccharide, named L2, obtained from L. edodes had shown anti‐ageing effects in mice. In this study, a 1H NMR‐based metabolomics approach was used to investigate the urinary metabolome changes in aged mice gavaged with L2 for better understanding of anti‐ageing mechanism. Six metabolites in urine were identified as potential markers for L2 treatment. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…In Asian countries, shiitake mushroom (Lentinus edodes) is one of the most economically important varieties of edible mushrooms owing to its unique flavor and texture. Furthermore, shiitake mushrooms have many beneficial effects on human health, including antitumor (Ya, 2017), antiaging (Xu et al, 2017), and antioxidant effects (Zhu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In Asian countries, shiitake mushroom (Lentinus edodes) is one of the most economically important varieties of edible mushrooms owing to its unique flavor and texture. Furthermore, shiitake mushrooms have many beneficial effects on human health, including antitumor (Ya, 2017), antiaging (Xu et al, 2017), and antioxidant effects (Zhu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, L2 reduced the diversity and evenness of gut microbiota in adult mice while elevating the diversity and evenness of gut microbiota in aged mice [19,22]. Further urinary metabolomic analysis also confirmed the differential physiological impacts of L2 on adult and aged mice [78,79]. The differences also suggested that the regulatory mechanism might be bacterial-specific since gut microbiota could modulate the protein expression exhibiting hetero-phenotypes in multiple tissues in mice [80].…”
Section: Discussionmentioning
confidence: 78%